(untitled) (Ustozlar uchun, 2025)
The main problem is that many countries care too much about PISA rankings instead of looking at students’ real skills and learning challenges. People get excited or worried about positions on the list, but few look at what the scores really tell about learning. In this essay, I will explain what PISA is, why focusing only on rankings is a problem, and how we can use the results to improve schools.